1992
DOI: 10.1111/j.1600-0773.1992.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloroquine on Some Carbohydrate Metabolic Pathways: Contents of GHS, Ascorbate and Lipid Peroxidation in the Rat

Abstract: Adult male rats were treated intraperitoneally with chloroquine (5 mg/kg/day) for 9 days. A reduction in the fasting plasma glucose level by 17.6% and ascorbic acid by 45% were discernable. The treatment caused significant increase in liver lactate dehydrogenase and glucose-6-phosphate dehydrogenase activities and reduced the activity of succinate dehydrogenase enzyme. Chloroquine also caused significant reductions in the contents of reduced glutathione and ascorbic acid in the brain and erythrocytes with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…Previous studies have indicated that plasma GSH as well as vitamin C and vitamin E were decreased in CQ treated rats and α-lipoic acid had a better protective effect than silymarin against CQ-induced hepatotoxicity (Abdel Gayoum et al, 1992;Pari and Murugavel, 2004); and our results are in agreement with these published reports. Preincubation of hepatocytes with vitamin C, quercetin and purpuragalin shows protective effects against CQ-induced toxicity in almost all parameters measured.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Previous studies have indicated that plasma GSH as well as vitamin C and vitamin E were decreased in CQ treated rats and α-lipoic acid had a better protective effect than silymarin against CQ-induced hepatotoxicity (Abdel Gayoum et al, 1992;Pari and Murugavel, 2004); and our results are in agreement with these published reports. Preincubation of hepatocytes with vitamin C, quercetin and purpuragalin shows protective effects against CQ-induced toxicity in almost all parameters measured.…”
Section: Discussionsupporting
confidence: 95%
“…A depletion of the antioxidant defense system is involved in the mechanism of cytotoxicity.inhibitor; quercetin a specific CYP2C8 inhibitor; quinidine and cimetidine, which inhibit the 2D6 subfamily; and acetone a non-specific CYP450 inhibitor on the cytotoxicity of CQ were investigated.There are few studies in the literature on the role of antioxidants against CQ-induced hepatotoxicity (Dass and Shah, 2000;Pari and Murugavel, 2004). Previous findings indicated that reduced glutathione (GSH), vitamin C and vitamin E were decreased in CQ-treated rats (Abdel Gayoum et al, 1992).The purpose of this study was to investigate the possible mechanisms of CQ hepatotoxicity on freshly isolated rat hepatocytes. As specific objectives, the experiments had in view (a) to evaluate the role and activity of CYP450 family metabolizing enzymes on CQ cytotoxicity, and (b) to test for effects of antioxidants, ATP supplier and cellular GSH in CQ-treated hepatocytes.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…According to previous reports, some authors suggested that the drug has inhibitory effect on metabolic pathways of glucose in parasites [8,9] where it was found to inhibit the uptake of glucose by schistosoma [10]. The drug was reported to decrease insulin and glucose levels in rats by interfering with insulin biosynthesis [11], decrease the rate of glucose oxidation in islets of Langerhans [12] and decrease fasting glucose level in rats treated with subchronic level of chloroquine [13]. Others suggested that chloroquine reduces intracellular insulin degradation in vitro [14] and in vivo [15] and inhibits 125 I-insulin degradation in the perfused rat liver [16].…”
Section: Introductionmentioning
confidence: 99%